Saint Thomas the Apostle: New Testament, Apocrypha, and historical traditions - Thomaskutty, Johnson (Jewish and Christian Texts, 2018)
Intro -- Title Page -- Copyright Page -- Contents -- Foreword: The Apostle Thomas and Christianityâs Mission to the East -- Acknowledgments -- Abbreviations -- Introduction -- Rationale, aim, and task -- Relevance of the study -- Thomas literature and traditions -- Twin motif of the Thomas Literature -- Research methodology -- Research plan -- Part 1: Thomas in the Gospel of John -- Chapter 1: From Lazarusâs Death to Jesusâs Death (11:1â12:11) -- Introduction -- Narrative setting -- Thomas within the narrative framework of Jn 11:1â12:11 -- Concluding remarks -- Chapter 2: Knowing the Way (13:1â17:26) -- Introduction -- Narrative setting -- Thomas within the narrative framework of Jn 13:1â17:26 -- Concluding remarks -- Chapter 3: Recognizing Jesus as âLordâ and âGodâ (20:1-31) -- Introduction -- Narrative setting -- Thomas within the narrative framework of Jn 20:1-31 -- Concluding remarks -- Chapter 4: Jesus Shows Himself (21:1-25) -- Introduction -- Narrative setting -- Thomas within the narrative framework of Jn 21:1-25 -- Concluding remarks -- Part 2: Thomas in the Apocryphal Documents -- Chapter 5: The Gospel of Thomas -- Introduction -- Synoptics and the Gospel of Thomas -- Log 1 -- Log 13 -- Thomasâs character: An analysis -- Concluding remarks -- Chapter 6: The Book of Thomas the Contender -- Introduction -- Ideological world of the Book of Thomas -- Thomas in the Book of Thomas -- Concluding remarks -- Chapter 7: The Acts of Thomas -- Introduction -- Thomas within the narrative framework of the Acts of Thomas -- The Indo-Parthian and South Indian theories -- The martyrdom of Thomas -- Concluding remarks -- Chapter 8: The Infancy Gospel of Thomas -- Introduction -- The Character of Thomas in the Infancy Gospel of Thomas -- Concluding remarks -- Part 3: Thomas in the Historical Traditions